Mitigating Agricultural Methane Emissions through Policy Reform: Long-Run Evidence from Indonesia’s Climate-Aligned Transition - Mega Amelia Putri; Syafruddin Karimi; Endrizal Ridwan; Fajri Muharja (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
Agricultural methane (CH₄) emissions remain a critical yet under-addressed component of global climate mitigation, particularly in tropical economies. This study investigates the long- and short-run drivers of CH₄ emissions from Indonesia’s agricultural sector between 1970 and 2022, focusing on three major sources: rice cultivation, enteric fermentation, and manure management. Using a dynamic econometric framework—including Autoregressive Distributed Lag (ARDL), Dynamic Ordinary Least Squares (DOLS), and Newey–West estimators—we quantify source-specific impacts and evaluate structural changes following post-2008 climate policy reforms. Results confirm rice cultivation as the dominant long-run contributor, where a 1% increase in CH₄ from paddy fields corresponds to a 0.72% rise in total agricultural methane emissions. Enteric fermentation and manure management also show significant effects, though to a lesser extent. A post-2008 policy dummy indicates a structural shift in emission dynamics, reflecting Indonesia’s transition toward climate-aligned agriculture through REDD+ and the National Action Plan for GHG Reduction (RAN-GRK). Short-run dynamics reveal corrective adjustments after emission shocks, highlighting system responsiveness to policy and environmental changes. The study underscores both the potential and the limitations of national mitigation efforts in reshaping long-term emission trends. Findings suggest that methane mitigation strategies—such as alternate wetting and drying (AWD) in rice farming and improved feed quality for livestock—can reduce emissions without compromising productivity. This study offers novel empirical insights for policymakers and climate practitioners seeking to integrate food security, sustainability, and low-emission agricultural development in emerging economies.